Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

The polynomial p(x)=x^3-19x-30 has a known factor of (x+2)

Rewrite p(x) as a product of linear factors


Sagot :

Answer:

(x+2) (x+3) (x-5)

Step-by-step explanation:

x³-19x-30 = (x+2) (x²+ax-15)  ... x³=x*(1*x²)   while -30= (2)*(-15)

x³ + 0*x² - 19x -30 = x³ + (2+a)x² + (2a-15)x -30

2+a = 0

a = -2

x³-19x-30 = (x+2) (x²-2x-15) = (x+2) (x+3) (x-5)

Answer:

[tex](x + 2)\, (x + 3)\, (x - 5)[/tex].

Step-by-step explanation:

Apply polynomial long division to divide [tex]p(x)[/tex] by the know factor, [tex](x + 2)[/tex].

Fill in the omitted terms:

[tex]\begin{aligned}p(x) &= x^{3}- 19\, x - 30 \\ &= x^{3} + 0\, x^{2} - 19\, x - 30\end{aligned}[/tex].

The leading term of the dividend is currently [tex]x^{3}[/tex]. On the other hand, the leading term of the divisor, [tex](x + 2)[/tex], is [tex]x[/tex].

Hence, the next term of the quotient would be [tex]x^{3} / x = x^{2}[/tex].

[tex]\begin{aligned}p(x) &= \cdots \\ &= x^{3} + 0\, x^{2} - 19\, x - 30 \\ &= x^{3} + 0\, x^{2} - 19\, x - 30 \\ &\quad - x^{2} \, (x + 2) + [x^{2} \, (x + 2)] \\ &= x^{3} + 0\, x^{2} - 19\, x - 30 \\ &\quad -x^{3} - 2\, x^{2} + [x^{2}\, (x + 2)] \\ &= -2\, x^{2} - 19\, x - 30 \\ &\quad + [x^{2} \, (x + 2)]\end{aligned}[/tex].

The dividend is now [tex](-2\, x^{2} - 19\, x - 30)[/tex], with [tex](-2\, x^{2})[/tex] being the new leading term. The leading term of the divisor [tex](x + 2)[/tex] is still [tex]x[/tex].

The next term of the quotient would be [tex](-2\, x^{2}) / x = -2\, x[/tex].

[tex]\begin{aligned}p(x) &= \cdots \\ &= -2\, x^{2} - 19\, x - 30 \\ &\quad + [x^{2} \, (x + 2)] \\ &=-2\, x^{2} - 19\, x - 30 \\ &\quad - (-2\,x ) \, (x + 2) + [(-2\, x) \, (x + 2)] + [x^{2} \, (x + 2)] \\ &= -2\, x^{2} - 19\, x - 30 \\ &\quad - (-2\, x^{2} - 4\, x) + [(x^{2} - 2\, x)\, (x + 2)] \\ &= -15\, x - 30 \\ &\quad + [(x^{2} - 2\, x)\, (x + 2)]\end{aligned}[/tex].

The dividend is now [tex](-15\, x - 30)[/tex], with [tex](-15\, x)[/tex] as the new leading term.

The next term of the quotient would be [tex](-15\, x) / x = -15[/tex].

[tex]\begin{aligned}p(x) &= \cdots \\ &= -15\, x - 30 \\ &\quad + [(x^{2} - 2\, x)\, (x + 2)] \\ &=-15\, x - 30 \\ &\quad -(-15)\, (x + 2) + [(-15)\, (x + 2)] + [(x^{2} - 2\, x)\, (x + 2)] \\ &= -15\, x - 30 \\ &\quad -(-15\, x - 30) + [(x^{2} - 2\, x - 15)\, (x + 2)] \\ &= (x^{2} - 2\, x - 15)\, (x + 2)\end{aligned}[/tex].

In other words:

[tex]\displaystyle \text{$\frac{x^{3} - 19\, x - 30}{x + 2} = x^{2} - 2\, x - 15$ given that $x+2 \ne 0$}[/tex].

The next step is to factorize the quadratic polynomial [tex](x^{2} - 2\, x - 15)[/tex].

Apply the quadratic formula to find the two roots of [tex]x^{2} - 2\, x - 15 = 0[/tex]:

[tex]\begin{aligned} x_{1} &= \frac{-(-2) + \sqrt{2^{2} - 4\times 1 \times (-15)}}{2} \\ &= \frac{2 + 8}{2}= 5\end{aligned}[/tex].

[tex]\begin{aligned} x_{2} &= \frac{2 - 8}{2} = -3\end{aligned}[/tex].

By the factor theorem, the two factors of [tex](x^{2} - 2\, x - 15)[/tex] would be [tex](x - 5)[/tex] and [tex](x - (-3))[/tex]. That is:

[tex]x^{2} - 2\, x -15 = (x + 3)\, (x - 5)[/tex].

Therefore:

[tex]\begin{aligned}p(x) &= \cdots \\ &= (x^{2} - 2\, x - 15)\, (x + 2) \\ &= (x + 2)\, (x + 3)\, (x - 5)\end{aligned}[/tex].

We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.